Association between visceral adiposity index and heart failure: A cross‐sectional study. Issue 3 (18th January 2023) - Zhang, Xinyu; Sun, Yijun; Li, Ying; Wang, Chengwei; Wang, Yi; Dong, Mei; Xiao, Jie; Lin, Zongwei; Lu, Huixia; Ji, Xiaoping
Abstract: Background: Obesity is an important risk factor for heart failure (HF). Hypothesis: Visceral adiposity index (VAI) is a simple metric for assessing obesity; however, the association between VAI and risk for HF has not been studied. Methods: A cross‐sectional study involving 28 764 participants ≥18 years of age from the National Health and Nutrition Examination Survey (NHANES), 2009–2018, in the United States was performed. VAI was calculated using body mass index (BMI), waist circumference (WC), triglycerides (TG), and high‐density lipoprotein cholesterol. VAI was analyzed as a continuous and categorical variable to examine its association with HF. Subgroup analysis was also performed. Results: The highest VAI (fourth quartile [Q4]) was found among males, BMI, systolic and diastolic blood pressure, WC, hypertension, diabetes, liver disease, coronary heart disease, smoking, total cholesterol, and TG. More participants in Q4 took β‐receptor blockers, angiotensin‐converting enzyme inhibitors/angiotensin II receptor blockers/angiotensin receptor‐neprilysin inhibitor, calcium channel blockers, and antidiabetic and antihyperlipidemic medications. Participants with HF exhibited greater VAI. A per‐unit increase in VAI resulted in a 4% increased risk for HF (odds ratio [OR] 1.04 [95% confidence interval (CI) 1.02–1.05]). After multivariable adjustment, compared with the lowest quartile, the OR for Q3 was 1.55 (95% CI 1.24–1.94). Subgroup analysis revealed no significant interactions between VAI and specific subgroups. Conclusion: VAI was independently associated with the risk for HF. As a noninvasive index of visceral adiposity, VAI could be used for a "one shot" assessment of HF risk and may serve as a novel marker.